2016
DOI: 10.1016/j.cell.2015.11.058
|View full text |Cite
|
Sign up to set email alerts
|

WNT-SHH Antagonism Specifies and Expands Stem Cells prior to Niche Formation

Abstract: Adult stem cell (SC) maintenance and differentiation are known to depend on signals received from the niche. Here however, we demonstrate a mechanism for SC specification and regulation that is niche-independent. Using immunofluorescence, live imaging, genetics, cell-cycle analyses, in utero lentiviral transduction, and lineage-tracing, we show that in developing hair buds, SCs are born from asymmetric divisions that differentially display WNT and SHH signaling. Displaced WNTlo suprabasal daughters become SCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
170
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 56 publications
10
170
0
Order By: Relevance
“…9C,D). In agreement with Ouspenskaia et al (2016), we observed that all HP divisions were oriented perpendicular to the BM, while a typical bimodal distribution was seen in the IFE (Fig. 9E).…”
Section: Potential Upstream Regulators Of Differential Lgn Localizationsupporting
confidence: 87%
See 2 more Smart Citations
“…9C,D). In agreement with Ouspenskaia et al (2016), we observed that all HP divisions were oriented perpendicular to the BM, while a typical bimodal distribution was seen in the IFE (Fig. 9E).…”
Section: Potential Upstream Regulators Of Differential Lgn Localizationsupporting
confidence: 87%
“…During embryogenesis, Lhx2 and Sox9 are among the earliest known transcription factors expressed in HPs, and are found in complementary patterns, with Lhx2 colocalizing with basal Pcad, and Sox9 positioned suprabasally (Rhee et al, 2006;Nowak et al, 2008 (Ouspenskaia et al, 2016). Genetic and lineage-tracing studies have shown that Sox9 + HFSCs specified during embryogenesis later take up residence in the bulge niche where they contribute to all postnatal HF lineages (Nowak et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correlated with GO-term analyses of WNT- Our data on FGFs further bolstered the importance of mesenchymal-to-epithelial signaling circuits for Shh suppression in foot skin. That said, Wnt signaling is required and upstream of Shh expression in hair buds (20,21) and is repressed in SwG buds (Fig. 4A and fig.…”
Section: All Roads Lead To Suppression Of Shh Signaling In Swg-permismentioning
confidence: 94%
“…That said, Wnt signaling is required and upstream of Shh expression in hair buds (20,21) and is repressed in SwG buds (Fig. 4A and fig.…”
Section: All Roads Lead To Suppression Of Shh Signaling In Swg-permismentioning
confidence: 99%